2020
DOI: 10.1111/anae.15327
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin complex concentrate vs. fresh frozen plasma in adult patients undergoing heart surgery – a pilot randomised controlled trial (PROPHESY trial)

Abstract: There is equipoise regarding the use of prothrombin complex concentrate vs. fresh frozen plasma in bleeding patients undergoing cardiac surgery. We performed a pilot randomised controlled trial to determine the recruitment rate for a large trial, comparing the impact of prothrombin complex concentrate vs. fresh frozen plasma on haemostasis (1 h and 24 h post-intervention), and assessing safety. Adult patients who developed bleeding within 24 h of cardiac surgery that required coagulation factor replacement wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 17 publications
3
50
1
Order By: Relevance
“…Secondly, lower doses of PCC (500 IU) and FFP (3 units) are suboptimal in correcting these abnormalities. Our data support the need for adequate clotting factor replacement therapies in cardiac surgical patients with complications of bleeding.We have shown that, for a range of haemostatic factors, a more balanced increase in clotting factors is seen with FFP compared with PCC[1], which is not surprising considering the content of both blood products. However, in this study,…”
supporting
confidence: 55%
“…Secondly, lower doses of PCC (500 IU) and FFP (3 units) are suboptimal in correcting these abnormalities. Our data support the need for adequate clotting factor replacement therapies in cardiac surgical patients with complications of bleeding.We have shown that, for a range of haemostatic factors, a more balanced increase in clotting factors is seen with FFP compared with PCC[1], which is not surprising considering the content of both blood products. However, in this study,…”
supporting
confidence: 55%
“…28 The variability in practice pertaining to administration of PCC vs FP should be explored further, and extends to the doses utilized by clinicians. Currently there is no clear consensus on the optimal dose of PCC for coagulopathy related to cardiac surgery, 17,29,30 with doses in our study ranging from 500 to 2,000 IU for a single administration. Given the significant differences in transfusion avoidance in favour of the PCC group in this study, our results suggest a dose between 1,000 IU and 2,000 IU is likely to be effective.…”
Section: Discussionmentioning
confidence: 95%
“…doses of 15-25 IUÁkg -1 (1,000-2,000 IU for an average sized patient), with observed hemostatic effects comparable with FP observed throughout this dose range, albeit in small numbers of patients. 29,30 This study builds on existing evidence and re-examines the efficacy of PCCs, while adding to the sparse published data on the safety of PCCs in the context of bleeding after cardiac surgery. Previously published work has been limited by small sample sizes, making comparisons of rare outcomes between groups difficult because of insufficient power.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations